Pengaruh Motivasi, Disiplin dan Kepemimpinan Terhadap Kinerja Pegawai Badan Pemberdayaan Perempuan Perlindungan Anak Dan Keluarga Berencana Kabupaten Banjar - Alfisah Alfisah (Universitas Lambung Mangkurat, 2013)
This study aims to determine the effect of motivation, work discipline, and leadership significantly of both simultaneously and partially on the performance of employees in women empowerment, Child Protection and Family Planning Board Banjar Regency. In addition, it also aims to find out the dominant variable affecting the performance of employees in Women Empowerment, Child Protection and Family Planning Board Banjar Regency. Sampling technique in this study is a census, wichh is all employees of Women Empowerment, Child Protection and Family Planning Board Banjar Regency as a population of 33 people were sampled. Data were analyzed using multiple regression analysis. The result showed that both partially and simultaneously, the variables motivation, work discipline, and leadership have a significant effect on the performance of an employee of Women Empowerment, Child Protection and Family Planning Board Banjar Regency. The most dominant variable affecting the performance of employee Women Empowerment, Child Protection and Family Planning Board Banjar Regency is the variable of work discipline. Variation of performance (y) which can be explained by the variables of moti- vation, work discipline, and leadership is at 66.7%, while the remaining 33.3% is influence by others.